Spiritual Aspects of Pregnancy and Childbirth Based on an Islamic Perspective - Trisiani, Desi; Ferina, Ferina; Indrayani, Diyan; H. Abdul-Mumin, Khadizah (Islamic Research, 2024)
A midwife adheres to a philosophy and has the belief that all human beings are unique bio-psycho- socio-cultural and spiritual beings who are a complete physical and spiritual entity and no two individuals are the same. The physical, psychological and spiritual synergy that is built during pregnancy has a significant impact on the outcome of labor. The role of religion as spirituality in this case maintaining human relations with the greatest power of Allah SWT, is an entity that cannot be negated in the management of pregnancy and childbirth care. Spirituality strongly affects Muslim women's behavior in caring for their pregnancy. The aim of this literature review study is to determine the effect of spiritual aspects on pregnancy and childbirth. Searches for qualitative and quantitative research published in peer reviewed journals were carried out through the PubMed, Elsevier and Google Scholar databases using a combination of the search terms "spiritual", "pregnancy", "childbirth" and "Islam" which were searched systematically. Publications selected for the final review covered a variety of research designs including experimental, case-control, phenomenological, cross-sectional, and ethnographic studies published between 2010 and 2022 and free full text articles, resulting in a final data set that included 15 studies. A spiritual approach to pregnancy has been shown to reduce stress in high-risk pregnancies and support normal delivery. Spirituality is a power from God that makes a woman confident about her health during pregnancy and childbirth and prevents excessive anxiety. A midwife should provide midwifery care holistically by paying attention to physical, mental, spiritual and social aspects in order to achieve optimal health and well-being. Attending to women's spiritual experiences during childbearing is an important way to enhance care.